2018
DOI: 10.1109/tdsc.2016.2615622
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optimal Countermeasure Selection for Intrusion Response System

Abstract: Abstract-Designing an efficient defense framework is challenging with respect to a network's complexity, widespread sophisticated attacks, attackers' ability, and the diversity of security appliances. The Intrusion Response System (IRS) is intended to respond automatically to incidents by attuning the attack damage and countermeasure costs. The existing approaches inherit some limitations, such as using static countermeasure effectiveness, static countermeasure deployment cost, or neglecting the countermeasure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Having discussed systems that recover from intrusions and showed that it is not enough to withstand them, we now discuss intrusion response systems [5,20,62] that focus on applying responses to limit the impact of an intrusion.…”
Section: Intrusion Response Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having discussed systems that recover from intrusions and showed that it is not enough to withstand them, we now discuss intrusion response systems [5,20,62] that focus on applying responses to limit the impact of an intrusion.…”
Section: Intrusion Response Systemsmentioning
confidence: 99%
“…One area of focus of prior work is on how to model intrusion damages, or response costs, to select responses. Previous approaches either rely on directed graphs about system resources and cost models [5], on attack graphs [20], or attack defense trees [62]. Shameli-Sendi et al [62] use Multi-Objective Optimization (MOO) methods to select an optimal response based on such models.…”
Section: Intrusion Response Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8] authors stated that use of common path mining helps hybrid IDS for better detection. Data mining is used for the building of a power system which operates on data logs.…”
Section: Literature Surveymentioning
confidence: 99%
“…en, appropriate defense strategies can be selected through cut-set analysis, game theory, and other methods. For example, Shameli-Sendi et al [13] used ADTree to establish a security model and then proposed a dynamic defense framework that selects an optimal countermeasure by considering the security benefit and attack damage cost. Wang and Liu [14] established a systematic attack defense game model based on the return on attack (ROA) and return on investment (ROI) of an ADTree.…”
Section: Introductionmentioning
confidence: 99%